PENDIDIKAN ISLAM MULTIKULTURAL, KERANGKA KONSEPTUAL, PERKEMBANGAN DAN DINAMIKA FENOMENA DAN TENDENSI MULTIKULTURAL - Zainuddin; Hairul Ulum (SIRAJUDDIN : Jurnal Penelitian dan Kajian Pendidikan Islam, 2024)
Based on the facts, increasing moral decadence and disgraceful behavior such asviolence, brawls, exclusivism and weak tolerance and respect for other people in all itsforms involving school children are real indicators of the ineffectiveness of the modeland function of Islamic education that has been implemented so far. Therefore, how tobuild an intelligent and moral Indonesia? How can Multicultural Islamic Educationchange the face of Indonesia to become a country that is very tolerant? This type ofresearch is qualitative research using the literature study method. The concepts andpractices of multicultural education in the United States can be applied in Indonesia tosupport education that prioritizes democratic methods. Multicultural education in theUnited States is closely related to diversity issues, so the possibility of implementing itin Indonesia is a challenge. The fact is that the legacy of the Suharto regime regardingthe prohibition on discussing SARA (ethnicity, religion, race and between groups) stillcontinues today. However, understanding the diversity and differences of students, inrelation to other groups, is very necessary in the context of multicultural education,especially to reduce prejudice and discrimination.